The Role of Nutrition Education in Increasing Public Awareness of Healthy Lifestyles: A Literature Study - Faradin, Anggia (Pt. Anagata Sembagi Education, 2025)
The increase in cases of non-communicable diseases such as obesity, hypertension, and diabetes shows the need for an education-based preventive approach, especially through nutrition education. This study aims to examine the role of nutrition education in increasing public awareness of healthy lifestyles through a qualitative approach with a literature study method. Data sources were obtained from 20 national and international scientific journals and publications over the past five years. The results of the study show that nutrition education has a significant impact on increasing public knowledge and attitudes towards the importance of consuming healthy foods. Interventions carried out through schools, social media, health services, and educational curricula have been shown to be able to shape better eating awareness and behavior. However, the effectiveness of nutrition education is greatly influenced by the delivery method, program consistency, and active community and cross-sector involvement. Challenges such as low nutritional literacy, limited experts, and the spread of misinformation in digital media are still major obstacles. Therefore, a contextual, participatory, and sustainable education strategy is needed so that nutrition education is not only an information tool, but also a means of social transformation to create a healthier society. These findings are expected to be the basis for formulating nutrition policies and intervention programs in the future.